2022
DOI: 10.1108/apjba-05-2021-0218
|View full text |Cite
|
Sign up to set email alerts
|

A nexus between intra-ASEAN outward FDI, intra-ASEAN exports and economic growth of ASEAN-10: evidence using panel causality analysis

Abstract: PurposeThe Association of Southeast Asian Nations (ASEAN) has evolved into ASEAN Economic Community (AEC), which aims to pursue a single market and production base to transform ASEAN into a dynamic, competitive and global region. ASEAN is inherently heterogeneous that potentially could promote further economic integration, fundamentally, through the interactions between intra-regional outward foreign direct investment (OFDI), export trade and economic growth. Hence, this paper attempts to explore the causal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…According to the estimation results, market size, tax rate, and labor expenses are the most important elements influencing a company's investment decision. In another study, Wong et al (2022) uncovered a bidirectional causality association between ASEAN exports and OFDI among ASEAN nations. Meanwhile, Ahmad et al (2018) revealed that the exchange rate and income were the most important factors influencing OFDI in ASEAN countries.…”
Section: Introductionmentioning
confidence: 97%
“…According to the estimation results, market size, tax rate, and labor expenses are the most important elements influencing a company's investment decision. In another study, Wong et al (2022) uncovered a bidirectional causality association between ASEAN exports and OFDI among ASEAN nations. Meanwhile, Ahmad et al (2018) revealed that the exchange rate and income were the most important factors influencing OFDI in ASEAN countries.…”
Section: Introductionmentioning
confidence: 97%
“…Zhang Xiaoling et al took the manufacturing industry in the Jiangsu Province as an example to analyze the relationship between manufacturing sectors in the process of outward direct investment, and made up for the gaps in research related to the sustainable development of China's outward direct investment from provincial data [13]. Foreign scholars studied the intraregional interaction between outward direct investment (OFDI), export trade and economic growth; they found that there is a causal relationship between export trade and economic growth for outward direct investment [14].…”
Section: Introductionmentioning
confidence: 99%